Revisiting Biodiversity and Ecosystem Functioning through the Lens of Complex Adaptive Systems - Alexandra M. Correia; Luís F. Lopes (Diversity, 2023)
Understanding the relationship between biodiversity and ecosystem functioning (BEF) is essential to comprehend the impacts of biodiversity changes on ecosystem functioning. This knowledge helps to detect and anticipate significant trends in global biodiversity loss and the homogenization of biota worldwide to prevent them. Species act together with climate, resource availability, and disturbance regimes to modulate ecological processes defining ecosystems’ complexity and their dynamic adaptation to variability. In this article, we revisit the BEF paradigm by addressing current knowledge of how biodiversity connects to ecosystem functioning across scales in the context of complex adaptive systems (CAS). We focus on ecosystem processes that lead to the emergence of the BEF relationship, considering ecosystem functioning as a macroscopic emergent property. Specifically, this work integrates the knowledge of the processes that connect biodiversity to ecosystem functioning. It addresses how biodiversity supports ecosystem multifunctionality across scales, resulting in the persistence of CAS in a rapidly changing world. We present a framework for ecological management considering the BEF relationship within the scope of CAS. The CAS standpoint brings new insights into the BEF field and its relevance for future ecological conservation of the Earth’s life support.